Perspective on healthy eating practices during 1000 days of life development: a qualitative study among female university students - Mohd Fauzi, Farah Raihana; Mohd Abu Bakar, Wan Azdie (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2022)
Introduction: Early life development is utmost important to ensure optimal growth and wellbeing. The main objective for this qualitative study is to explore the perspectives of female university students on the healthy eating practice for maternal health and child development during the first 1000 days of life. Method: The study was conducted by using focused group discussion (FGD) with a total of 24 participants in which there were 4 groups of students consisting of 5-7 participants in a group. Result: This study found that there are various factors that took a role as barriers and/or knowledge in the perspectives of female university students toward healthy eating practice. The barriers include behaviour of parents and child, economic status, lifestyle, physiological aspects of mother and child, and time constriction. Family and social media influences served as both barriers and source of knowledge while other sources of information were television and formal education. The participants also characterized the importance of food intake into three themes namely the macronutrients, micronutrients, and types of food. Conclusion: This study indicates that the female university students have some good understanding on the barriers and facts on nutrition for maternal health and child development. For future research, the study can be extended to the male population of university students to get the perspectives of future fathers.